Outcome analysis of immediate and delayed laparoscopic pyeloplasty in infants with severe ureteropelvic junction obstruction - Bao, Qiao; Ma, Weijun; Zhang, Xiewu; Chen, Shuhan; Luo, Jiayao; Zhang, Gang; Lao, Weihua; Chen, Yueqing (Frontiers in Pediatrics, 2022)
Objective: The treatment timing of ureteropelvic junction obstruction (UPJO) in infants remains controversial. This study aimed to compare the recovery effect of renal morphology of immediate and delayed laparoscopic pyeloplasty in infants with severe UPJO. Methods: The infants with severe UPJO-induced hydronephrosis who underwent laparoscopic pyeloplasty according to their age at the time of surgery [the immediate treatment (IT) group: ≤ 1 month of birth, the delayed treatment (LT) group: 3-6 months of birth] in our center between 2010 and 2019 were enrolled in this study. Ultrasonography was used to assess renal morphology, including anteroposterior diameter (APD) of a pelvic, parenchymal thickness (PT), polar length (PL), and Society of Fetal Urology (SFU) grade. Preoperative and postoperative renal morphological outcomes at 6, 12, and 24 months were measured and compared. Results: During this period, a total of 135 patients were assigned to receive either IT (n =73) or LT (n = 62) and were included for analysis. There were no significant differences in renal morphology indices at baseline between groups of IT and LT. The APD, PT, and PL in both groups all recovered to certain degrees compared with those at baseline, however, the IT group recovered more significantly than the LT group. Despite there being no significant difference in SFU grade between the two groups before and after surgery, the reduction of SFU grade in the IT group was more significant than that in the LT group during the 6-, 12- and 24-month follow-up periods. The PL, SFU, and APD were greater in the IT group than in the LT group at 6, 12, and 24 months of follow-up. At 6 months PL was not significantly higher between the two groups, while the outcome was significantly different at 12 months and 24 months. Conclusion: Immediate laparoscopic pyeloplasty for the infant with severe ureteropelvic junction obstruction is effective, and it can accelerate the recovery of renal morphological indices in infants with severe UPJO-induced hydronephrosis.